SISTEM KEAMANAN WEB DENGAN MENGGUNAKAN KRIPTOGRAFI MESSAGE DIGEST 5/MD5 PADA KOPERASI MITRA SEJAHTERA BANDUNG - Asep Ririh Riswaya; . Komarudin (STMIK Mardira Indonesia, Bandung, 2015)
A security issue for the company’s website is very important to manage carefully because the statistics of information held by the company. By using cryptography is expected to be one of the alternatives in maintaining security in this cooperative website Prosperity Partners Bandung by applying cryptographic MD5. Application that was built using Object Oriented Approach method Development Life Cycle (OODLC) as well as the approach to object-oriented software paradigm Unified Modeling Language (UML). Keywords: web protection system; cryptography; system administration